Towards a Tika Political Science: Restoring Balance, Reflecting Our Context - Azarmandi, M; Beausoleil, E; Bickerton, SH; Choi, S; Fadgen, T; Greener, B; Gregory, T; Hayward, J; Lovering, I; Nissen, S; Powles, A; Sardelić, J; et al. (The University of Queensland, 2024)
This article is a rejoinder to Annie Te One and Maria Bargh’s article published in The Australian Journal of Indigenous Education in 2023, “Towards a Fairer and More Tika Political Science and Politics: Are Political Science Programs Equipping Students Adequately for Aotearoa Realities?” (vol. 52, no. 2).
Keywords: 3902 Education Policy, Sociology and Philosophy; 3903 Education Systems; 39 Education; 1301 Education Systems; 1303 Specialist Studies in Education; 1608 Sociology; 3902 Education policy, sociology and philosophy; 3903 Education systems